2011
DOI: 10.1111/j.1525-139x.2011.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphate Binder Equivalent Dose

Abstract: Phosphate binders include calcium acetate or carbonate, sevelamer hydrochloride or carbonate, magnesium and lanthanum carbonate, and aluminum carbonate or hydroxide. Their relative phosphate-binding capacity has been assessed in human, in vivo studies that have measured phosphate recovery from stool and/or changes in urinary phosphate excretion or that have compared pairs of different binders where dose of binder in each group was titrated to a target level of serum phosphate. The relative phosphate-binding co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(80 citation statements)
references
References 39 publications
2
77
0
1
Order By: Relevance
“…10) Another way to consider the impact of this largely unrecognized source of dietary phosphorus is to consider it in terms of the number of phosphorus binding tablets required to block the absorption of an amount of dietary phosphorus equivalent to that in the phosphorus-containing drug. One tablet of sevelamer (800 mg) binds ~25.5 mg of phosphorus, whereas a cap-sule of calcium acetate (667 mg) binds ~28.5 mg. 10,16) Thus, simply to bind the phosphorus in the two tablets of paroxetine and amlodipine noted above, this unlucky patient would require additional doses of sevelamer or calcium acetate. Further, a signiˆcant fall oŠ in adherence to binder therapy might occur as the pill burden increases.…”
Section: Discussionmentioning
confidence: 99%
“…10) Another way to consider the impact of this largely unrecognized source of dietary phosphorus is to consider it in terms of the number of phosphorus binding tablets required to block the absorption of an amount of dietary phosphorus equivalent to that in the phosphorus-containing drug. One tablet of sevelamer (800 mg) binds ~25.5 mg of phosphorus, whereas a cap-sule of calcium acetate (667 mg) binds ~28.5 mg. 10,16) Thus, simply to bind the phosphorus in the two tablets of paroxetine and amlodipine noted above, this unlucky patient would require additional doses of sevelamer or calcium acetate. Further, a signiˆcant fall oŠ in adherence to binder therapy might occur as the pill burden increases.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Pi binders that can reduce serum Pi with the smallest dose are desirable and preferred. Adherence to Pi binder therapy was recently reported to be the best with Ca carbonate, followed by LaC and sevelamer hydrochloride (20). In that study, patient preference was mostly related to gastrointestinal side effects and the drug dosage.…”
Section: Discussionmentioning
confidence: 93%
“…Lanthanum was selected because studies of phosphate-binding in humans have shown that lanthanum has the highest relative phosphate-binding coefficient (RPBC) in comparison to other phosphorus binders, and hence has a lower pill burden [17]. Although animal studies have shown that lanthanum may accumulate in organs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in the high-protein hemodialysis meal group also received 0.5-1.5 g of lanthanum carbonate with each meal box that was titrated every 2 weeks as necessary. Lanthanum carbonate was specifically selected given its high phosphate-binding capacity and low pill burden compared with other phosphorus binders [17]. Patients assigned to the low-protein hemodialysis meal group received prepared boxes containing meals with minimal protein (<1 g), <20 mg phosphorus and low caloric (<50 kcal) content, such as salads, during the first 60 min of each hemodialysis treatment over the study period (see Supplementary data).…”
Section: Study Interventionmentioning
confidence: 99%